Application of Make A Match Type to Improve Student Learning Outcomes in SDN Batiombo 02 - Surtini, Surtini (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve science learning achievement in the material Classification of Animals based on their Food through the Scientific approach with the Make A MActh Strategy for grade V 1st semester students of SDN Batiombo 02, Bandar District, Batang Regency, 2020/2021 academic year. This research is a Classroom Action Research through three learning processes carried out through pre-cycle stages on October 22, Cycle I on November 16, 2020 and Cycle II on November 23, 2020. The results of learning improvements are from the initial conditions before the action only 3 students ( 30%) who completed with KKM 70, in the first cycle learning completeness increased to 10 students (67%). Through cycle II student learning completeness again increased to 14 students (93%) of the total number of grade 5 students.Thus, through the scientific approach, Make A Macth strategy can increase students' understanding of Animal Classification material based on food in grade V semester 1 SDN Batiombo 02 District Bandar Batang Regency Academic Year 2020/2021.